Physical activity and body mass shape quality of life trajectories in mid‐age women - Jeeva Kanesarajah; Michael Waller; Jennifer A Whitty; Gita D Mishra (Elsevier, 2018)
Abstract Objective: To determine the combined longitudinal effect of body mass index (BMI) and physical activity (PA) on health‐related quality of life (HrQoL), using the SF‐6D (SF‐36) utility measure. Methods: Five waves of self‐reported data from the 1946-51 cohort (n=5,200; data collection, 2001-2013) of the Australian Longitudinal Study on Women's Health were used. Mixed effect models were employed to address the objective. Results: Women with high PA experienced higher HrQoL regardless of BMI group, however, for those healthy or overweight, there was a very small decline in HrQoL over time. Women reporting no PA levels experienced the lowest baseline mean SF‐6D score within each BMI group, with decreasing trajectories over the follow‐up period. The rate of decline was greatest in women with obesity. Within each BMI group, there was a large, increasing gap in HrQoL between those who reported no and low PA over time. Women with obesity and high PA experienced similar HrQoL trajectories to women with normal weight or overweight with low PA levels. Overweight women with moderate PA experienced similar HrQoL to those with low PA but normal weight. Conclusions: PA may mitigate the adverse effect of overweight and obesity on HrQoL at mid‐life, at higher activity levels. Implications for public health: PA benefits HrQoL regardless of body mass, with larger gains for those currently not physically active. Moderate to high PA may mitigate the effect of overweight and obesity.